I. M. D. Little, Tibor Scitovsky, Maurice Scott. Industry and trade in some developing countries :a comparative study. París : OCDE, Centro de Estudios de Desarrollo, 1970. 512 p. - Alejo, Francisco Javier (Estudios Demográficos y Urbanos, 1971)
I.M.D. LITTLE, TIBOR SCITOVSKY, MAURICE SCOTT, Industry and Tratte in Some Developing Countries. A Comparative Study, París, OCDE, Centro de Estudios de Desarrollo, 1970.